Nurses' Perspectives on Challenging Nursing Practices for Patients with Acute Stroke in Japan - Hisaka, Yukari; Blaquera, Allan Paulo; Soriano, Gil; Ito, Hirokazu; Yasuhara, Yuko; Matsumoto, Kazuyuki; Bollos, Leah Anne Christine; Tanioka, Ryuichi; Takase, Kensaku; Tanioka, Tetsuya (Celebes Nursing Journal, 2024)
Introduction: Nurses in acute stroke units constantly face complex illness conditions that demand advanced understanding and effective execution of specialized nursing care. Objective: This study aimed to identify nursing practices that nurses find challenging to execute for patients with acute stroke. Method: The participants of this study were 1,040 nurses working in 53 stroke units in Japan. A survey was conducted from February to March 2021. The data used in this analysis were open-ended responses to the question “content of difficult nursing practices and causes of these difficulties in the care of patients with acute stroke.” These responses were analyzed by morphological analysis of text data mining using MeCab. Also, qualitative inductive analysis was performed by the researchers. Result: Seven categories were extracted: 1) caring for family members, 2) rehabilitation to improve patients’ activities of daily living, 3) life guidance after discharge, 4) reliable nursing practice, 5) protection of patients’ human rights, 6) physical management, and 7) understanding patients’ feelings. The nurses recognized the need to provide patients and their family with discharge counseling, rehabilitation, and nursing guidance in activities of daily living to improve independence and prevent the recurrence of stroke. Patient safety and well-being are ensured when nurses are able to fully comprehend the patient’s physical and mental conditions. Conclusion: hospitals should provide nurses with continuing education and a support system to ensure that they possess the necessary competencies in the management of patients with acute stroke.